Mulheres que gestam nas ruas e suas vivências de cuidado: estudo à luz da fenomenologia heideggeriana - Barros, Keila Cristina Costa (2019)
Introduction: Taking a close look at the condition of being pregnant and existing on the streets, insurge triple exclusion: being a woman, black and being on the street. This exclusionary reality manifests itself through stigma and marginalization, and exposes a specific and heterogeneous social condition. Objective: to understand the experience of pregnancy care, from the perspective of homeless women in the municipality of Feira de Santana - BA. Method: qualitative, descriptive approach. It was based on the phenomenology of Martin Heidegger, adapted to the health area. Ten interviewees participated, who met the inclusion criteria: women who lived or experienced the gestational period in the street situation; age over 18 years; reside in public spaces of the municipality; and exclusion: women with mental and / or emotional problems that prevented them from participating in the interviews. The technique of data collection and production was the phenomenological interview, through a semi-structured script, applied from March to May 2019. The comprehensive analysis took place by the methodical moments: reduction, construction and phenomenological destruction. The research is linked to the Center for Research and Extension in Women's Health of the State University of Feira de Santana. It has approval from the ethics committee with opinion 2,686,905. Results: from the comprehensive analysis three units of meaning emerged: being on the streets being a woman; experiences of women who gestate in the streets; care from the perspective of pregnant women on the street. The existence of women in a situation of representing beings thrown into the world, with difficulties, discrimination, violence, prejudice, racism and vulnerability and experiencing pregnancy in this context is degrading, configuring a violation of human dignity, unveiling the singularities and nuances of the woman-triad. maternity-street. Care proved fragile and precarious, both in self-care and by managers and health professionals, which reveals risk for mother and child. Final considerations: It is believed that it is possible that pregnant women in homeless situations can experience care, based on the implementation of effective public policies, trained professionals, and managers aware of their singularities. These pregnant women are street lives, represent fractures and social vulnerabilities of existence. Contributions: for the service, it enabled the elaboration of the flowchart of Nursing Care for Pregnant Women in Street Situation - Feira de Santana - BA 2019, with the purpose of enabling the care, valuing and giving visibility to the unique conditions of pregnancy of such women, as well as point out ways for comprehensive and sensitive care, from the perspective of ensuring access to quality prenatal care. In the social sphere, it may arouse the sensibility of society, the authorities responsible for public safety and the realization of their right to health. In the academic universe, it will be possible to broaden the debate on the assistance to pregnant women in homeless situations, based on a body of knowledge built with a Heideggerian phenomenological perspective, to enable and transverse this theoretical construction with the formulation, implementation and implementation of public policies.